Securing Delay-Tolerant Networks with BPSec - Birrane (Wiley Data and Cybersecurity, 2023)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing